Proposing a New Model of Knowledge Innovation for Research University Based on Entrepreneurial Paradigm - Mustapha, Ramlee (EDUCARE, 2010)
ABSTRACT: The emergent entrepreneurial paradigm has led to the increasing role of the research university in knowledge innovation, hence making entrepreneurial research university a global phenomenon. Research universities are expected to provide intellectual innovations for the economic and societal advancement. It is argued that to ensure an effective achievement of research universityâs objectives, appropriate definition and model must be identified. This article attempts to propose a generic model of knowledge innovation for the research university. It identifies the definitions of the research university, knowledge innovation, and best practices of the established research universities. It then looks into the process of knowledge creation and innovation in research universities. Based on the review of literature, this article proposes a model of knowledge innovation for the research university by integrating knowledge innovation framework and the simplified Triple Helix Model. The focus of this article, however, is on the knowledge innovation. Knowledge innovation is most relevant in the context of research university. Literature also indicates that there are two forms of innovation, namely, incremental and radical innovations.KEY WORDS: knowledge innovation, research university, Triple Helix Model, and entrepreneurial paradigm.About the Author: Professor Dr. Ramlee B. Mustapha is a Lecturer at the Faculty of Education UKM (National University of Malaysia); and also as the Director of the Centre of Excellence for Learner Diversity (CELD) at the Faculty of Education UKM, 43600 Bangi, Selangor Darul Ehsan, Malaysia. He can be reached at: drramlee@yahoo.comHow to cite this article? Mustapha, Ramlee B. (2010). âProposing a New Model of Knowledge Innovation for Research University Based on Entrepreneurial Paradigmâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.111-130. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 15, 2009); Revised (January 25, 2010); and Published (February 17, 2010).